Prepare for the Future: Dissecting the Spike to Seek Broadly Neutralizing Antibodies and Universal Vaccine for Pandemic Coronaviruses - Vangelista, Luca; Secchi, Massimiliano (Frontiers in Molecular Biosciences, 2020)
Learning from the lengthy fight against HIV-1, influenza and Ebola virus infection, broadly neutralizing antibodies (bnAbs), directed at conserved regions of surface proteins crucial to virus entry (Env, hemagglutinin, and GP, respectively), are an essential resource for passive as well as active immunization. Rare in their emergence and antigen recognition mode, bnAbs are active towards a large set of different viral strains. Isolation, characterization and production of bnAbs lead to their possible use in passive immunotherapy and form the basis for an educated effort in the development of vaccines for universal coverage. SARS-CoV-2-specific antibodies targeting the spike receptor binding domain (RBD) may lead to antibody dependent enhancement (ADE) of infection, possibly hampering the field of vaccine development. This perspective points to the identification of conserved regions in the spike of SARS-CoV-2, SARS-CoV and MERS-CoV through investigation, dissection and recombinant production of isolated moieties. These spike moieties should be capable of independent folding and allow the detection as well as the elicitation of bnAbs, thus setting the basis for an effective passive immunotherapy and the development of a universal vaccine against human epidemic coronaviruses (HCoVs). SARS, MERS and, most of all, COVID-19 demonstrate that humanity is the target of HCoV, preparedness for future hits is thus no longer an option.